Insulin resistance in cardiovascular disease, uremia, and peritoneal dialysis. (September 2021) - Lambie, Mark; Bonomini, Mario; Davies, Simon J.; Accili, Domenico; Arduini, Arduino; Zammit, Victor
Abstract : Diabetic nephropathy is highly correlated with the occurrence of other complications of type 1 diabetes (T1D) and type 2 diabetes (T2D) mellitus; for example, hypertension with cardiovascular disease (CVD) being the most frequent cause of death in patients with end-stage renal disease and undergoing renal dialysis. Hyperglycemia and insulin resistance (IR) are responsible for the micro- and macrovascular complications of diabetes through different mechanisms. In particular, IR plays a key role in the etiology of atherosclerosis in both diabetic and non-diabetic patients. IR – exacerbated by organ-level selectivity – is more important than glycemic control per se in determining cardiovascular outcomes. This may be exacerbated by the fact that IR is organ and pathway specific due to the only selective loss of sensitivity to insulin action of specific pathways/processes. Therefore, it is counterintuitive that the use of peritoneal dialysis (PD) in (frequently) diabetic renal disease patients should involve their exposure to high daily doses of glucose peritoneally. In view of the controversy about the causal association between glucose load and CVD in PD patients, we discuss the role that selective IR may play in the progression of CVD in diabetic renal end-stage patients. In discussing these associations, we propose that reducing glucose exposure in PD solutions may be beneficial especially if coupled with strategies that address IR directly, and the avoidance of excessive use of insulin treatment in T2D. Highlights: Diabetic patients undergoing peritoneal dialysis (PD) are exposed to high dose of glucose throughout the day. Insulin resistance (IR) exacerbates the effects of the insulin secretagogue effects of high glucose exposure. Selective IR between tissues and pathways amplifies the effects of selected pathways of insulin signaling remaining active under conditions of increased hyperglycemia and hyperinsulinemia. Selective insulinemia in the endothelium and nephrons may increase the cardiometabolic risk. PD solutions that substitute glucose partly for other osmolytes such as xylitol and L-carnitine may offer a strategy to minimize the risks of induction of selective IR.